2020
DOI: 10.1098/rstb.2020.0077
|View full text |Cite
|
Sign up to set email alerts
|

The role of female reproductive fluid in sperm competition

Abstract: The role of non-gametic components of the ejaculate (seminal fluid) in fertility and sperm competitiveness is now well established. Surprisingly, however, we know far less about female reproductive fluid (FRF) in the context of sexual selection, and insights into male–FRF interactions in the context of sperm competition have only recently emerged. Despite this limited knowledge, evidence from taxonomically diverse species has revealed insights into the effects of FRF on sperm traits that have previously been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 94 publications
3
67
0
6
Order By: Relevance
“…R. Soc. B 375: 20200082 gametic interactions when sperm are locked in competition (as appreciated in other taxa; see [103]). Indeed, mammals have a clear role to play in uncovering new and exciting discoveries as we embark on the next 50 years of studying the fascinating phenomenon that is sperm competition.…”
Section: Resultsmentioning
confidence: 99%
“…R. Soc. B 375: 20200082 gametic interactions when sperm are locked in competition (as appreciated in other taxa; see [103]). Indeed, mammals have a clear role to play in uncovering new and exciting discoveries as we embark on the next 50 years of studying the fascinating phenomenon that is sperm competition.…”
Section: Resultsmentioning
confidence: 99%
“…Our experimental design enables us to conclude that these effects can be driven exclusively by egg-derived substances from different females. Such substances, broadly termed FRFs, are widespread across taxa and a growing body of evidence suggests they commonly mediate gamete interactions ( [19], see [52,53]). Our results provide important complementary evidence to previous findings that components of the ejaculate can similarly drive nongenetic effects [15][16][17]; together, these studies suggest that gamete-level interactions among different males and females could represent a more widespread source of nongenetic variance in offspring fitness than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…For example, reproductive fluids derived from the female reproductive tract or eggs can differentially affect sperm motility and physiology (e.g. capacitation and acrosome reaction) among ejaculates from different males [18,19], which provides the potential for females to bias fertilizations towards preferred males [20][21][22]. Similarly, under conditions of sperm competition, a male's seminal plasma can differentially affect the motility of own and rival sperm depending on the identities of both males [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear if sperm grouping within an ejaculate is random or if certain cells (e.g., slower sperm) tend to group together, thereby forming slower aggregates. Moreover, because the viscosity female reproductive fluids in Peromyscus are unknown, it is not clear how they compare to our artificial suspension media or if they differ among species, thus we are limited in our interpretation of how sperm aggregation influences movement in the female reproductive fluids (Gasparini et al 2020). In addition, a recent study reported that cell-cell interactions may be important for sperm migration through environments that mimic the highly-folded epithelium of the mammalian female reproductive tract (Bukatin et al 2020).…”
Section: Discussionmentioning
confidence: 99%